DETERMINATION OF URANIUM AND THORIUM SURFACE DISTRIBUTION IN GEOLOGICAL SAMPLES: COMPARISON OF TABLETOP MACRO AND MICRO-XRF SCANNING. Issue 9 (22nd August 2022) - Trojek, Tomáš; Trojková, Darina; Mikysek, Petr
Abstract: This paper describes the identification and quantification of uranium, thorium and other chemical elements in a low-grade uranium ore, using macro and micro-X-ray fluorescence scanning. The result of such scanning is their surface distribution determined in flat samples. The basic parameters of both setups are described. The investigation was focused mainly on the improvement of the lateral resolution in the laboratory tabletop macro-XRF and its comparison with micro-XRF scanning. A standard reference material NIST 610 was used as a homogeneous reference silicate material of a known composition. The measurements have demonstrated how the macro-XRF with a quite wide X-ray beam can be competitive with the micro-XRF scanning. The capabilities of both devices were established, utilizing measurements of selected uranium-bearing sediments samples, from the Břevniště deposit in the Czech Republic.